A Model Of Vocational Competency Assessment Of Industrial Engineering Students Of Vocational High Schools - Muhammad Akhyar (JOURNAL OF EDUCATION, 2009)
This study aims to develop a model of competency assessment. The research population consisted of two subpopulations, namely (1) engineering and vocational education experts, machinery practice instructors, and industry practitioners, and (2) students of Industrial Engineering Vocational High Schools in Surakarta. The sample from the first subpopulation was selected using the purposive sampling technique and that from the second subpopulation was selected using the proportional random sampling technique. The data were collected through questionnaires, a paper-and-pencil test, and a performance test. The data were analyzed using the descriptive technique and the LISREL model analysis. The results show the following. First, the construct model consists of the learning style construct, personality construct, and competency construct. Second, there is a positive and significant relationship between students personality and learning style, students learning style and personality, students learning style and vocational competency, and there is a negative and significant relationship between students personality and vocational competency. The model of vocational competency development fits the empirical data. Third, the model of vocational competency assessment consists of three components, namely personality, learning style, and competency. The model is called the PLC model. Keywords: assessment model, competency, vocational school